Analysis of Changes in Community Consumption Patterns for Fast Food and Obesity - Sabrina, Bianca (Mandalika Journal of Medical and Health Studies, 2025)
Socio-economic changes and urban lifestyles have driven shifts in food consumption patterns, with an increasing preference for fast food. In Indonesia, this phenomenon is one of the main contributors to the increasing prevalence of obesity, especially in the productive age group. This study aims to analyze changes in people's consumption patterns for fast food and their implications for the prevalence of obesity. The approach used is a qualitative literature study by reviewing academic sources and empirical data from the last five years (2019–2024) obtained from various databases such as PubMed, Scopus, and Google Scholar. The analysis method used is thematic content analysis to identify key themes such as fast food consumption trends, driving factors, and health impacts. The results of the study show that fast food consumption has increased significantly among urban communities, driven by practical factors, media influence, and aggressive marketing. This consumption is positively correlated with an increase in body mass index (BMI) and obesity prevalence, as reflected in Riskesdas data showing an increase in obesity prevalence from 14.8% in 2013 to 21.8% in 2018. In addition, high fast food consumption is generally accompanied by a sedentary lifestyle and low nutritional awareness. These findings indicate the importance of policy interventions based on nutritional education, advertising restrictions, and healthy lifestyle promotion to suppress the increasing obesity trend in Indonesia.